Production analysis in environmental, resource, and infrastructure evaluation - Shunsuke Managi; George Halkos (Journal of Economic Structures, 2015)
Over the past several decades, significant efforts have been made to regulate the use of resource and pollution in most industrialized countries, and the stringency of pollution regulations has continued to increase globally. At the same time, physical and social infrastructures are influenced by changes in the use of resources which contribute to the wealth of many regions. Technical progress plays an important role in maintaining a high standard of living in the face of these increasingly stringent regulations. This thematic series looks at how recent advances in this field to contribute to understanding the evaluation for environment, resource, and infrastructure management.
Keywords: O10; O13; O18; Q01; Q40; Q50; 330